Assessing the importance of pedagogical abilities Çf table tennis coaches in the context of achieving high results of PRC sportsmen - Ernie, Go; Ryzhkova, L.G. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to assess the level of significance of pedagogical abilities, the manifestation of which allows table tennis coaches to achieve high results in the preparation of Chinese athletes. Methods and structure of the study. The work was attended by 100 table tennis coaches, each of whom acted as an expert. The examination was aimed at identifying the opinions of coaches on assessing the significance of the types of pedagogical abilities that affect the athletic performance of the trainees. The experts were asked to note at what level of significance a particular pedagogical ability is manifested in the training of athletes. Results and conclusions. The results of the expert survey allow us to state that in order to achieve high results in the preparation of athletes, coaches must be endowed with certain pedagogical abilities. The respondents named didactic, personal and authoritarian abilities as especially important (“very significant”). Constructive, expressive, organizational, communicative and special abilities are distinguished as no less significant (“more significant than less”). It should be noted that a third of the experts do not believe that academic abilities affect the effectiveness of training athletes, since they singled out these abilities as “less significant than more” and “little significant”.